Applications of Platelet-rich Plasma in the Treatment of Musculoskeletal Injuries - Thi Thanh, Pham; Thi Mai, Nguyen; Thi Ngoc Ha, Nguyen; Thi Hien, Mai; Dac Tu, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 39 No 3, 2023)
The use of platelet-rich plasma (PRP), which has the ability to hasten the repair of soft tissue, cartilage, and bone, has revolutionized musculoskeletal medicine. Applications include treatment of osteoarthritis, tendinopathy, chondropathy, acute and chronic soft tissue injuries, muscle or ligament tears, as well as enhancement of healing of cartilage joints. With the ability to promote safe and natural healing, PRP is considered a promising alternative to surgery. Recently, there is an emerging literature on the beneficial effects of PRP for chronic non-healing tendon injuries and cartilage degeneration. This review article provides an overview of recent basic science and clinical studies on the applications of PRP to the treatment of musculoskeletal injuries.